Model Hubungan Politik Era Pemerintahan Jokowi: Mengkaji Peran Media dan Partisipasi Publik - Gun Gun Heryanto (Jurnal Communicate, 2015)
Phenomenon of governance Joko Widodo (Jokowi) is about a model of political relations between actors. Interaction takes place between the ruling elite (state actors) and the community (society actors). Therefore, it is difficult to avoid when the then competition between the interests of the ruling elite and society become dominant in the political process, both at the decision-making and policy implementation. In the exercise of power, it is used to turn up and gained four patterns of political interaction that is complementary patterns, accommodate, compete with and replace. Is asymmetrical relationship model that is not too clear who the opponent and friend. Political cooperation often take the option koopsi the cause potential swingers in the coalition. This, due to the lack of a dominant winning party in the middle of a strong fragmented multiparty system (a highly fragmented Multiparty system) so that all parties would prefer a consensus democracy. In the midst of the crush various issues, public participation is often expressed through mass media and social media. This can be understood as non-conventional forms of political participation.